Beginning PHP : master the latest features of PHP 7 and fully embrace modern PHP development - Carr, David; Gray, Markus (Packt Publishing, 2018)
In this book, you'll learn everything you need to get up and running with the latest version of PHP, including package management with tools such as composer, secure database operations, and a whole host of other best practices that will help you stay a step ahead of traditional programmers. What you will learn: Understand the fundamentals of PHP and work with classes and inheritance; Learn about database operations and package management with composer; Tackle common security concerns and pitfalls using authentication and validation; Build effective PHP applications and frameworks for your business needs. Who this book is for: If you're already familiar with another programming language and want to learn about the fundamentals of PHP programming, you'll find the flow of this book to be an ideal fit. Having a prior understanding of HTML, MySQL, CSS, and JavaScript will be beneficial, but is not mandatory.